Optimization of the structure of special strength training in qualified athletes doing crossfitt - Yurchenko A.L.; Razzhivin O.A.; Dorontsev A.V.; Kukochkina I.V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to optimization of the structure of special strength preparedness among qualified athletes involved in crossfit. Methods and structure of the study. Results of test tasks for special strength preparedness (barbell clean, barbell snatch, barbell bench press, barbell squat, shot throw with two hands back, 200 m run with a 30 kg load, standing triple jump, standing long jump, upward jump standing, pull-ups on the bar) in qualified athletes were determined using standard methods. 41 young men of the second and first sports categories, CMS Sports School of Moscow, took part in the research. Results and conclusions. With the growth of sports skills, the levels of strength preparedness of those involved significantly increased, and the coefficients of variation decreased, the number of reliable relationships between indicators of special strength readiness decreased, and the specificity of the relationship structure also appeared. The work calculated the correlation coefficients of indicators of special strength readiness of those involved in various sports qualifications, and checked their suitability in the process of sports training. The importance of the optimal structure of special strength preparedness among qualified athletes involved in crossfit is traced.